Fundamentos de teoria de grupos e aplicações ao jogo Resta Um - Santos, Epifanio Lima (2015)
This paper aims to present an methodology of teaching of algebra associated to the geometry, based on the theory of symmetry groups D4 with emphasis on the Klein group, as perceive that the game structure "peg solitare"has the same principles governing the Klein theory associated with symmetry group D4; so we explored the teaching resources offered by this popular game to introduce basics of groups and the relationship between their algebraic and geometric aspects, making them accessible to high school students.